Rediscovery of Phlogacanthus jenkinsii (Acanthaceae) from India after 140 years - Maity, Rohan; Sawmliana, Mal; Dash, Sudhansu Sekhar (Phytotaxa, 2022)
Phlogacanthus jenkinsii C.B. Clarke (Acanthaceae: Andrographideae), a poorly known species in India, is recollected after 140 years from Mizoram. A detailed taxonomic description along with a photo plate, illustration and comparative diagnostic characters with closely allied species are provided in the present communication.